Determination of the Ratios of Ligands to Metal Ion of some Metal Complexes of Triazoles by Using Eleetronie Speetra in Organie Solvents - Baghdad Science Journal (مجلة بغداد للعلوم)
We found that 4,5- diphenyl- 3(2- propynyl) thio- 1??-triazole [1? forms a complex with Pd (11) ion of ratio 1:1 which absorbs light in CH2CI2 at 400 nm, and 4,5- diphenyl- 3(2- propenyl) thio- 1,2,4- triazole [II] forms complexes with Pd (II) ion of ratio 1:1 which absorbs light at 390 nm, and of ratio 2:1 which absorbs light at 435 nm. On the other hand, we found that the new derivative 4- phenyl- 5( p- amino phenyl) -3- mercapto- 1,2,4- triazole ?111? forms complexes with Cu (II) ion of the ratio 1:1 which absorbs light at 380 nm, with Ni (II) ion of the ratio 3:1 which absorbs light at 358 nm; and with Co (11) ion of the ratio 3.2:1 which absorbs light at 588 nm. The ratio of the complexes were determined by measuring the electronic spectra of the complexes in CH2G2 and (CH^NCHO at different concentrations ofthe ligands and f?xed ' •' of the metal ion in every case, then applying the molar ratio plots on the data. Our results were confirmed by precipitating most ofthe above complexes in solid state, and then each complex was analyzed elementally.